AN IMPLEMENTATION OF E-LEARNING BASED MOODLE TO DEVELOP MATHEMATICAL COMMUNICATION SKILL AND SELF-EFFICACY - Linda Astriani; Dewi Setiyaningsih; Misriandi Misriandi; Anggi Yuliani (KALAMATIKA Jurnal Pendidikan Matematika, 2021)
Mathematical communication skills are important, and education should facilitate students to improve their mathematical communication skills. The purpose of this study was to develop e-learning based on Moodle to improve students' mathematical communication and self-efficacy and student self-efficacy and describe how to students’ mathematic communication and student self-efficacy. This study used mixed-method research. The population in this study were Year 5 students at a private primary school. Data collection techniques used in this study are observation and tests. The implementation with Moodle was effective to the students’ mathematic communication and self-efficacy student. Overall, the students’ mathematical communication skills and self-efficacy of students using E-learning based Moodle is better than those using conventional learning. Also, self-efficacy positively affects students' communication skills with a very strong correlation coefficient, meaning that the higher students' self-efficacy, the higher students' communication skills.